EFFICACY OF TWO REGIMENS OF DEXAMETHASONE FOR MANAGEMENT OF PRETERM LABOUR: PILOT STUDY - Rasool, Ahsan; Farooq, Umer; Nazir, Qurat ul Ainn; Durrani, Hira Bahar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Dexamethasone is widely used for prevention of respiratory distress syndrome (RDS), necrotising enterocolitis (NEC) and intra-ventricular haemorrhage (IVH) in preterm babies; decreasing the neonatal mortality rate. There is no consensus on the dose of corticosteroid administered to the mother expected to have a preterm baby. This study is conducted to compare the effectiveness of two popular regimens of dexamethasone administration in decreasing incidence of RDS, necrotizing enterocolitis, IVH and neonatal mortality rate. Methods: Randomized control trial was conducted at Ayub Teaching Hospital, Abbottabad from 1st to 31st August, 2014. Sample size was set at 50. Block randomization was employed in the trial to allocate the patients into corresponding groups ’˜A’ and ’˜B’. Group A was administered 6mg dexamethasone in 4 doses 12 hours apart and group B was administered 2 doses 12 hours apart. Results: Forty-eight patients participated in the study with 24 patients in each group. Mean age and period gestation of participants were 28.4 years±4.3 SD and 34 weeks±1.9 SD respectively. Four patients in group A gave birth to neonate with RDS compared to two cases in group B. Group B had higher incidence of necrotizing enterocolitis and neonatal mortalities. However, none of these differences observed were statistically significant. No case of IVH was reported in either of the groups. Conclusion: Both the popular regimens of dexamethasone administration are equally effective in decreasing the incidence of neonatal diseases. Keywords: dexamethasone; preterm babies; respiratory distress syndrome; necrotizing enterocolitis; intra-ventricular haemorrhage